Does the boycott affect Israel-affiliated companies in Indonesia? - Nurman Ilham Fadzilah; Lenni Yovita; Dwi Eko Waluyo; Vicky Oktavia (Publikasi Inspirasi Indonesia, 2024)
This study aims to analyze changes in abnormal returns and trading volume Activity (TVA) before and after the announcement of MUI Fatwa Number 83 of 2023 on companies that are targeted for boycott and allegedly affiliated with Israel. The researcher used an event study approach with an event window of 100 days before and 100 days after the announcement of MUI Fatwa Number 83 of 2023 to calculate abnormal returns and trading volume activity. The analysis step carried out in this study is to test the normality of the data first to see if the data has been distributed normally or not, then to test the hypothesis. For normally distributed data, the Paired Sample T-test will be used and the normally undistributed data will use Wilcoxon Signed Rank. The results of this study showed that there was no significant difference in abnormal returns before and after the boycott, but there was a significant difference in trading volume activity before and after. These findings reflect that the boycott has no significant impact and the impact of the boycott is only temporary. However, the action reacted to changes in market sentiment due to the boycott that affected the trading of shares of the boycotted target companies.